Fundamental problems in the peer-review process and stakeholders' perceptions of potential suggestions for improvement - Kadaifci, Cigdem; Isikli, Erkan; Topcu, Y. Ilker (Wiley, 2024)
Academic papers are essential for researchers to communicate their work to their peers and industry experts. Quality research is published in prestigious scientific journals, and is considered as part of the hiring and promotion criteria at leading universities. Scientific journals conduct impartial and anonymous peer reviews of submitted manuscripts; however, individuals involved in this process may encounter issues related to the duration, impartiality, and transparency of these reviews. To explore these concerns, we created a questionnaire based on a comprehensive review of related literature and expert opinions, which was distributed to all stakeholders (authors, reviewers, and editors) who participated in the peer-review process from a variety of countries and disciplines. Their opinions on the primary issues during the process and suggestions for improvement were collected. The data were then analysed based on various groups, such as gender, country of residence, and contribution type, using appropriate multivariate statistical techniques to determine the perceptions and experiences of participants in the peer-review process. The results showed that unethical behaviour was not uncommon and that editors and experienced reviewers encountered it more frequently. Women and academics from Türkiye were more likely to experience ethical violations and perceived them as more ethically severe. Incentives and stakeholder involvement were seen as ways to enhance the quality and impartiality of peer review. The scale developed can serve as a useful tool for addressing difficulties in the peer-review process and improving its effectiveness and performance.
Keywords: factor analysis; peer review; scientific journals; academic papers